Strategi Komunikasi Guru Sekolah Minggu Dalam Menumbuhkan Motivasi Belajar Firman Tuhan Anak Sekolah Minggu Gmim Yesus Memberkati - Jeremia Wakas; Glory Virginia Sampel (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2023)
The purpose of this study was to analyze the communication strategies of Sunday school teachers in cultivating motivation to study God's Word for Sunday school children GMIM Yesus Memberkati Manado Winangun Region. To examine the communication strategy using the communication model according to Lasswell's propaganda theory by analyzing the sources, messages, media, recipients, and effects of the communication process. This study used a descriptive qualitative method with data collection techniques through observation, interviews and documentation. The results of the research show that the right communication strategy can increase the motivation of Sunday school children to learn God's Word. The communicator must have credibility and ability to prepare material before sharing the Word of God. The main message that the communicator wants to convey is the Word of God by maximizing verbal and non-verbal communication according to the needs of Sunday school children. The media and learning models used are varied. Through face-to-face, they include telling stories, role playing, using visual aids such as pictures and tools that illustrate the story of God's Word. Besides that, there are also digital media such as digital storytelling and motion videos and songs that support learning God's Word. The communicants are GMIM Yesus Memberkati Sunday school children ranging in age from 0 to 12 years. The effect of the communication process implemented is the growth of motivation to study God's Word as seen from the enthusiasm and enthusiasm of the Sunday school children when listening to stories of God's Word in worship activities.